The End? Christian Eschatology and the End of the World. (January 2016) - Case-Winters, Anna
Scientific pictures of the world's future portray a definite endpoint to life as we know it. How do we think about this reality theologically in relation to Christian hope? What do these visions of "the end" mean in relation to our understanding of divine purposes (ends)? A robust Christian eschatology includes honest grappling with these difficult questions.